Evaluating the Effect of Chemical Digestion Treatments on Polystyrene Microplastics: Recommended Updates to Chemical Digestion Protocols. Issue 13 (25th March 2022) - Gulizia, Alexandra M.; Brodie, Eve; Daumuller, Renee; Bloom, Sarah B.; Corbett, Tayla; Santana, Marina M. F.; Motti, Cherie A.; Vamvounis, George
Abstract: Establishing the toxicity and exposure consequences of microplastics (MPs) on marine organisms relies on the nondestructive isolation of plastics from biological matrices. MPs are commonly extracted from these matrices by chemical digestion using alkali (e.g., potassium hydroxide (KOH) and sodium hydroxide (NaOH)), oxidative (e.g., hydrogen peroxide (H2 O2 )) and/or acidic (e.g., nitric acid (HNO3 )) reagents. Although these digestion conditions can be highly effective for MP extraction, they can also react with the plastics. This can attribute an inaccurate representation of plastic contamination by altering MP visual characteristics (size, shape, color), thereby impeding identification and potentially returning erroneous numbers of ingested particles. In this study, the degradative impacts are assessed of the routinely applied digestion reagents (i) KOH, (ii) NaOH, (iii) H2 O2, and (iv) HNO3 on polystyrene (PS) based MPs sized between 200 µm and 5 mm. Degradation of the PS MPs is evaluated using FT‐IR, gel permeation chromatography, NMR, photoluminescence spectroscopy, and microscopy. These studies reveal HNO3 to be the most destructive for PS MPs, while the alkali and oxidative reagents result in negligible changes in plastic properties. These results are recommended to be used as a guideline to update current protocols to ensure the nondestructive treatment of MPs. Abstract : The suitability of common alkali, oxidative, and acidic digestion treatments from polystyrene‐based microplastics (200 µm – 5 mm) are evaluated. This research characterises changes to the physical and chemical properties of the microplastic polymer, which are critical for their efficient extraction accurate and identification postdigestion. Researchers can now be directed towards appropriate, nondestructive digestion protocols for the recovery of microplastics from their biological sample matrices.